"The Autobiography of Fadwa Touqan, the Question of Identity an the Origins of Feminist Conscienseness: a Critical Study: the “Mountainous Journey” –and the “More Difficult Journey (Damascus University Journal of arts and humanities sciences, 2021)
The autobiography of Fadwa Touqan is still one of the most prominent feminist autobiographies in Arabic literature, and it unveils many of the issues of the Arab women and their suffering within a patriarchal male-dominant society, which deals with women with extreme cruelty and arbitrariness. Fadwa Touqan criticized this situation severely, trying to prove her identity and femininity in this context. This is what the current study aims at presenting, while discovering features of Touqan's autobiography, and her subjective and objective impulses to write the autobiography. The current study also aims at reflecting the similarities between Touqan's opinions and the opinions of feminist critics as well as the differences between them.